Amiodarone as an Antiarrhythmia Therapy can Induce Acute Renal Failure in Patiens with SupraventricularTachycardia (SVT): A Rare Case Report - Nurjanah, Melany; Haryadi, Haryadi (Faculty of Medicine, Universitas Andalas, 2025)
Amiodarone is classified as a class III antiarrhythmic agent that primarily inhibits adrenergic stimulation by blocking alpha and beta-adrenergic receptors. This drug also affects sodium, potassium, and calcium channels and prolongs the action potential and refractory period in myocardial tissue. Amiodarone, a drug well known for its wide range of side effects, can also affect the kidneys. The incidence of amiodarone-induced acute kidney failure is rare. There are limited studies regarding kidney injury caused by amiodarone. It has been reported a 45-year-old woman was admitted with leiomyoma and was scheduled for surgery. During hospitalization, the patient complained of palpitations that had been continuously present for one day. Electrocardiographic examination showed supraventricular tachycardia. The patient received intravenous amiodarone therapy followed by oral amiodarone. Renal function test results showed a decline after the patient received amiodarone therapy for 24 hours. The supraventricular tachycardia converted to normal sinus rhythm. After amiodarone was discontinued for several days, renal function returned to normal significantly. Keywords: acute kidney injury, amiodarone, renal toxicity